Mercury desorption from contaminated sediments - Duarte, A. C.
The effects of pH and ionic strength on the release of Hg from contaminated coastal sediments to water were evaluated in a series of laboratory experiments. Data show that the higher the ionic strength and the pH the smaller is the amount of Hg desorbed into solutions. The effect of the ionic strength on the leaching of Hg from contaminated sediments is more evident for values lower than 0.4 mol dm−3, while the influence of pH becomes more pronounced for values lower than 7. Based on qualitative concepts from colloid chemistry an attempt is made to provide an explanation of the observed results.